2023
DOI: 10.1038/s41386-023-01574-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lysergic acid diethylamide (LSD) on whole-brain functional and effective connectivity

Abstract: Psychedelics have emerged as promising candidate treatments for various psychiatric conditions, and given their clinical potential, there is a need to identify biomarkers that underlie their effects. Here, we investigate the neural mechanisms of lysergic acid diethylamide (LSD) using regression dynamic causal modelling (rDCM), a novel technique that assesses whole-brain effective connectivity (EC) during resting-state functional magnetic resonance imaging (fMRI). We modelled data from two randomised, placebo-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Besides the well-established roles of GABA A receptors, emerging evidence has identified this very specific subunit as a promising therapeutic target for addressing a wide spectrum of neurological and neuropsychiatric disorders (65,66). Interestingly, functional magnetic resonance imaging (fMRI) studies suggest that LSD perturbs the excitation/inhibition balance of the brain (67). On the other hand, OGA is an enzyme that mediates the removal of O-GlcNAc from target proteins (68).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the well-established roles of GABA A receptors, emerging evidence has identified this very specific subunit as a promising therapeutic target for addressing a wide spectrum of neurological and neuropsychiatric disorders (65,66). Interestingly, functional magnetic resonance imaging (fMRI) studies suggest that LSD perturbs the excitation/inhibition balance of the brain (67). On the other hand, OGA is an enzyme that mediates the removal of O-GlcNAc from target proteins (68).…”
Section: Resultsmentioning
confidence: 99%
“…Other work has also demonstrated that the psychedelic DMT amplifies bottom-up travelling waves while reducing the power of top-down travelling waves. While there have been an abundance of studies on undirected FC under psychedelics (Barrett, Doss, et al, 2020; Barrett, Krimmel, et al, 2020; Bedford et al, 2023; R. L. Carhart-Harris et al, 2016; Dai et al, 2023; Gaddis et al, 2022; Grimm et al, 2018; Madsen et al, 2021; Mason et al, 2020; Palhano-Fontes et al, 2015; Pallavicini et al, 2019; Roseman et al, 2014; Timmermann et al, 2023), there have been relatively few studies on directed FC by comparison (Alamia et al, 2020; Barnett et al, 2020; de Araujo et al, 2011; Timmermann et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…When we initially looked at the pairwise FC matrices from the studies that we included in the meta-analysis, we were surprised to find that the increases in within-DMN FC outnumbered the decreases. This result was mostly driven by three studies that performed whole-brain seed-to-seed FC analyses (Bedford et al, 2023; Dai et al, 2023; Timmermann et al, 2023). However, we subsequently discovered that many of the regions in these studies overlapped with other Yeo networks besides the DMN.…”
Section: Discussionmentioning
confidence: 99%